Attractive and healthy-looking male faces do not show higher immunoreactivity - Pátková, Žaneta; Schwambergová, Dagmar; Třebická Fialová, Jitka; Třebický, Vít; Stella, David; Kleisner, Karel; Havlíček, Jan (Scientific reports, 2022)
Previous research has indicated that facial attractiveness may provide cues to the functioning of the immune system. Mating with individuals who have a more effective immune system could lead to a higher reproductive success. Our main aim was to test a possible association between immunoreactivity (stimulated by vaccination) and perceived facial attractiveness and healthiness. We experimentally activated the immune system of healthy men using vaccination against hepatitis A/B and meningococcus and measured levels of specific antibodies (markers of immune system reactivity) before and 30 days after the vaccination. Further, 1 day before the vaccination, we collected their facial photographs that were judged by females for attractiveness, healthiness, and facial skin patches for healthiness. In view of its proposed connection with the functioning of the immune system, we also measured skin colouration (both from the facial photographs and in vivo using a spectrophotometer) and we assessed its role in attractiveness and healthiness judgements. Moreover, we measured the levels of steroid hormones (testosterone and cortisol) and the percentage of adipose tissue, because both are known to have immunomodulatory properties and are related to perceived facial attractiveness and healthiness. We found no significant associations between antibody levels induced by vaccination and perceived facial attractiveness, facial healthiness, or skin healthiness. We also found no significant connections between steroid hormone levels, the amount of adipose tissue, rated characteristics, and antibody levels, except for a small negative effect of cortisol levels on perceived facial healthiness. Higher forehead redness was perceived as less attractive and less healthy and higher cheek patch redness was perceived as less healthy, but no significant association was found between antibody levels and facial colouration. Overall, our results suggest that perceived facial attractiveness, healthiness, and skin patch healthiness provide limited cues to immunoreactivity, and perceived characteristics seem to be related only to cortisol levels and facial colouration.
Keywords: obličej; Female; krása; zdravotní stav; Beauty; Humans; ženské pohlaví; Face; mužské pohlaví; Male; lidé; Judgment; Health Status; Hydrocortisone; hydrokortison; mínění